Body Alteration of Patients with Tuberculosis who Get Medication at the Public Health Centre - Suprajitno Suprajitno; Sri Mugianti (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2020)
Patient with tuberculosis who already experience 6 months of treatment may felt body alteration. The study aimed to illustrate the body alteration of Tuberculosis patients who got medication at the Public Health Centre. The design of the study used cross sectional. The sample was 141 tuberculosis patients who got medication at the Public Health Centre in Blitar which was selected by simple random sampling. The variables were height, weight, urine color, feeling of bored related to the medication and willingness to stop taking the medication routinely. The data was collected at the patient's home on August - November 2018. The data was collected by instruments of height gauge, weights, and interview form. The data was analyzed descriptively. The results showed that most of the changes were in the physical such as the weight loss, the red urine, and nausea. The patient's nausea caused a decrease in intake and had an impact on the patient's weight that went down. It is important for nurses in Public Health Centre to provide medical services and information through health education before the first medication.